Mosque Architecture in Cyprus—Visible and Invisible Aspects of Form and Space, 19th to 21st Centuries - Marko Kiessel; Asu Tozan (Religions, 2021)
A comprehensive analysis of Cypriot mosque architecture between the 19th and 21st centuries, from the Ottoman and British colonial periods to the present, does not exist. The phase after 1974, after the division of the island into a Turkish Cypriot, predominantly Muslim north and a Greek Cypriot, mainly Christian south, is especially insufficiently studied. This paper aims to interpret Cypriot mosque architecture and its meaning(s) through a comparative analysis, considering cultural, religious, and political developments. Based on an architectural survey and studies about Muslim Cypriot culture, this study investigates formal and spatial characteristics, focusing on the presence/absence of domed plan typologies and of minarets which, as visual symbolic markers, might express shifting cultural-religious notions and/or identities. Inconspicuous mosques without domes and minarets dominate until 1974. However, with the inter-communal tensions in the 1960s, the minaret possibly became a sign of Turkish identity, besides being a cultural-religious marker. This becomes more obvious after 1974 and is stressed by the (re)introduction of the dome. Since the late 1990s, an ostentatious and unprecedented neo-Ottoman architecture emphasizes visible and invisible meanings, and the Turkish presence in Cyprus stronger than before. The new architectural language visually underlines the influences from Turkey that North Cyprus has been experiencing.